Implementation of Rainwater in Preparatory Processes as well as Dyeing of Knitted Cotton Fabric and Compare the Effects with Ground Water - Alom, Md Samiul; Badhon, Farjana; Halder, Shompa Rani; Saha, Tonmoy (Chemical Engineering Research Bulletin, 2021)
Textile industries are very much intensive to water. A large amount of water is consumed every day during various textile processes and one of the main sources of this water is groundwater. This project aimed to work with rainwater which can be an alternative source of groundwater. In this project, the quality of rainwater was evaluated first and matched with the standard. From different tests such as turbidity, water hardness, amount of dissolved solids, and iron content, we found that the rainwater achieved the standard level of dye house water supply. After that, different wet preparatory processes, as well as dyeing of cotton fabric were carried out using rainwater. After completion of each process, evaluation was carried out such as weight loss percentage and absorbency for scouring, whiteness index for bleaching, and colour fastness tests of dyed fabric. The results were excellent compared with conventionally groundwater treated fabric. Chemical Engineering Research Bulletin 21(2020) 54-59